Navigating Cultural and Religious Identity through Arabic and English Language Education: Students' and Teachers' Perspectives - Suparmanto; Muhsinin; Ruwaida (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study examined student and instructor opinions of the unique roles that Arabic and English play in influencing cultural and religious identities within Indonesian pesantren, institutions that endeavor to reconcile traditional Islamic education with global expectations. This study used a qualitative research paradigm to perform a comprehensive analysis of the relationship between language acquisition and identity development within the pesantren setting. This study utilises a case study methodology to perform a thorough uation of how pesantren institutions incorporate Arabic and English training to foster cultural and religious identity. The study utilized questionnaires distributed to 111 students and 8 teachers to determine the impact of various languages on identity formation. Research consistently indicates that Arabic is regarded as essential for religious identity and cultural preservation; pupils strongly associate it with faith and legacy, a perspective unanimously supported by educators. In contrast, English exhibited a complex representation. Although acknowledged for its worldwide prospects and influence on personal identity, many students encountered difficulties in preserving their religious and cultural identity while acquiring English language skills. Educators also recognized this dual function of English. Notwithstanding these conflicts, a significant majority of students contended that bilingualism in both languages eventually enriches their entire identity. This study emphasizes the necessity for a balanced, culturally sensitive teaching that recognizes Arabic's fundamental significance while deliberately incorporating English to cultivate strong, multidimensional identities that are grounded in heritage and engaged worldwide.